EFFECTIVE SCHOOL FOR SOCIETY IN EDUCATION - Tengku Darmansah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
Effective school formation is not separated from the shared roles of all theschool residents, ranging from principals, teachers, staff, schoolcommittees, students, parents, and other stakeholders. School is aneffective school that performs its functions as a good learning place inproviding quality learning services for students by demonstrating thesuitability between the expected results and the results achieved.